2017
DOI: 10.1017/jan.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Actigen™ to sows during gestation and lactation and on piglet performance

Abstract: SummaryActigen™ is a second generation, unique bioactive fraction derived from the outer cell wall of a specific strain of yeast, Saccharomyces cerevisiae, where it acts in the gut to bind pathogenic bacteria, preventing disease and competition for nutrients. In the current trial, 260 sows were used and fed either an unsupplemented control diet or one containing Actigen™ at 0.08% of the formulation during gestation, farrowing and lactation, to assess its impact on sow and piglet performance. Results showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…[ 31 ]. However, a few recent studies revealed that sow dietary YD supplementation during gestation had no effect on the average numbers of piglets born and those born alive [ 1 , 5 , 32 ]. It has been reported that live born litter size is mainly determined by the fertilization rate and embryonic mortality during early pregnancy [ 33 ], and therefore supplementing the sow diet with YD during gestation might not have had an effect on the litter size as we report.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ]. However, a few recent studies revealed that sow dietary YD supplementation during gestation had no effect on the average numbers of piglets born and those born alive [ 1 , 5 , 32 ]. It has been reported that live born litter size is mainly determined by the fertilization rate and embryonic mortality during early pregnancy [ 33 ], and therefore supplementing the sow diet with YD during gestation might not have had an effect on the litter size as we report.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast products are typically utilized in nursery diets with the objective of improving the rate and efficiency of growth, as well as enhancing overall animal health. They have sometimes been included in sow diets in an attempt to improve litter performance ( Taylor-Pickard et al, 2017 ). In an extensive summary of peer-reviewed publications on the topic of growth-promoting antibiotic alternatives and covering the period from 1990 to 2016, Schweer et al (2017) reported that 24% of studies with yeast products reported an improvement in ADG, 12% in ADFI and 11% in feed efficiency.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 99%